Platinum-doped CeO2 thin film catalysts prepared by magnetron sputtering - Matolín, V; Matolínová, I; Václavů, M; Khalakhan, I; Vorokhta, M; Fiala, R; Pis, I; Sofer, Z; Poltierová-Vejpravová, J; Mori, T; Potin, V; Yoshikawa, H; et al. (Langmuir, 2010)
The interaction of Pt with CeO(2) layers was investigated by using photoelectron spectroscopy. The 30 nm thick Pt doped CeO(2) layers were deposited simultaneously by rf-magnetron sputtering on a Si(001) substrate, multiwall carbon nanotubes (CNTs) supported by a carbon diffusion layer of a polymer membrane fuel cell and on CNTs grown on the silicon wafer by the CVD technique. The synchrotron radiation X-ray photoelectron spectra showed the formation of cerium oxide with completely ionized Pt(2+,4+) species, and with the Pt(2+)/Pt(4+) ratio strongly dependent on the substrate. The TEM and XRD study showed the Pt(2+)/Pt(4+) ratio is dependent on the film structure.